Impaired endocytosis may represent an obstacle to gene therapy in polycystic kidney disease - Witzgall, Ralph; Kränzlin, Bettina; Gretz, Norbert; Obermüller, Nicholas (Kidney international, 2002)
Impaired endocytosis may represent an obstacle to gene therapy in polycystic kidney disease. - Background - Autosomal-dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disease and a frequent cause of chronic renal failure. The cloning of the PKD1 and PKD2 genes, which are mutated in the great majority of patients with this disease, opens up the opportunity for somatic gene therapy by introduction of the wild-type gene or cDNA. Several publications have provided evidence, that many portions of the nephron and the collecting duct can form cysts, including the proximal tubule. Alterations in the proximal tubule may prevent the efficient endocytosis of filtered proteins and thus contribute to proteinuria, a frequent symptom in patients with polycystic kidney disease. At the same time this may also negatively affect various gene therapy strategies, since endocytosis is important for the uptake of foreign DNA at least under some circumstances. In the (cy/+) rat, a widely used animal model for ADPKD, cysts almost exclusively develop from proximal tubules, and we have therefore investigated whether proteinuria and defective endocytosis also occur in this model. - Methods - Proteinuria was demonstrated by direct measurement and by protein gel electrophoresis of urines from 16 week-old (cy/+) rats. Endocytosis was investigated by injection of FITC-dextran and immunohistochemical staining with anti-ClC-5 and anti-megalin antibodies. - Results - Similar to the observations made in ADPKD patients, proteinuria also develops in the (cy/+) rat. Using FITC-labeled dextran as an in vivo tracer for renal tubular endosomal function, we could show that portions of cyst-lining epithelia from proximal tubules have lost the ability to endocytose, which is necessary for the reabsorption of albumin and lower-molecular-weight proteins. By immunohistochemistry the expression of other proteins implicated in endocytosis, such as the chloride channel ClC-5 and the albumin receptor megalin, correlated well with the presence and absence of FITC-dextran in cyst wall epithelia. - Conclusion - These data indicate that proteinuria and albuminuria in the (cy/+) rat model for ADPKD are due to a loss of the endocytic machinery in epithelia of proximal tubular cysts. Such a defect may also reduce the efficacy of certain gene therapy protocols.
Gesehen am 28.06.2022